The Project Boomerang: Evaluating Factors and Challenges in Learner’s Reading Performance - Sardina, Dante; Bohol, Sherie; Magrata, Blessy; Naval, Matthew; Sultan, Sittin (Asian Journal of Community Services, 2025)
This study investigates all the challenges and factors affecting the learners' of East Tapinac in terms of their reading performance, especially those difficulties related to alphabetic knowledge, reading comprehension, emotional responses to reading, as well as the effectiveness of teaching strategies employed by the students' teachers of Gordon College, BSEd English. The mixed-method approach adopted for the present study understands such difficulties with a representative sample of young readers by merging qualitative observations and interviews with the learners. The study suggests that the various challenges confronting the struggling reader demand a multi-modal approach with frequent reading practice and bespoke treatments. These findings add to making more effective literacy programs so that children can become proficient readers.